1985
DOI: 10.3181/00379727-179-rc3
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Athymic Nude Mice for the Study of Human Keloids

Abstract: A b s t r a c t : Keloid t i s s u e h a s been implanted i n t h e athymic nude mouse i n o r d e r t o develop a n experimental animal model f o r t h e s t u d y o f human k e l o i d s and h y p e r t r o p h i c s c a r s . Untreated k e l o i d t i s s u e s maintained e s s e n t i a l l y t h e same morphological p a t t e r n s and glycosaminoglycan d i s t r i b u t i o n s f o r a t l e a s t 60 days a f t e r i m p l a n t a t i o n i n t h e athymic mice. Normal human s k i n implanted i n t h e s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…A major reason for this has been that proliferative scar formation is limited to humans and is difficult to study systematically. This has been overcome by using the congenitally athymic nude mouse [3][4][5] and rat [6]. Recently, a new in vivo model of human proliferative scar explanted to a sandwich-island flap, maintained on an isolated accessible vasculature in a "nude" rat, was developed by our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…A major reason for this has been that proliferative scar formation is limited to humans and is difficult to study systematically. This has been overcome by using the congenitally athymic nude mouse [3][4][5] and rat [6]. Recently, a new in vivo model of human proliferative scar explanted to a sandwich-island flap, maintained on an isolated accessible vasculature in a "nude" rat, was developed by our laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…However, few keloid scar models have been developed in animals that mimic human keloid pathology (7,8). The scar model of the nude mouse was first established by Sheltlar et al, who found that the scar pieces transplanted to the subcutaneous of the nude mouse was able to be maintained for long time and showed similar histological properties in the body (9). However, the process of model establishment was complicated and apt to have deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronologically, the athymic mouse model was developed ®rst, followed by the development of the athymic rat model. 13,14 The merits of each model must be carefully considered prior to experimentation. Tables II and III outline the characteristics and advantages and disadvantages of each athymic rodent model.…”
Section: Animal Modelsmentioning
confidence: 99%